Pengaruh Penerapan Manajemen Risiko Terhadap Kinerja Keuangan Triwulan 2016 – 2020 Pada Bank Pembangunan Daerah Jawa Timur - Harun Al Rasyid; Syukron Sazly (Owner : Riset dan Jurnal Akuntansi, 2021)
Importance The role of banking is currently very dominant with the financial system. A good financial system will have a positive effect on banking performance. This study aims to determine the effect of banking risk which is analyzed using the ratio of NPL, NIM, LDR, BOPO on financial performance with ROA at the Regional Development Bank of East Java. The data used in this study were obtained from annual published financial reports from the website ojk.go.id. The number of samples is 20 East Java Regional Development Banks with a quarterly period from 2016-20202. This study uses the SSS method where the results of the research show that the determinant coefficient (R2) shows the Adjusted R Square number of 0.988 or 98.8%, which means that variations in the level of financial performance can be explained by NPL, NIM, LDR and BOPO on ROA, the remaining 1.2 % can be explained from other variables outside the research variables. For the research results simultaneously, NPL, NIM, LDR, and BOPO have a significant effect on ROA. The effect partially for NPL Risk (X1) does not have a significant negative effect partially on ROA (Y), for NIM risk (X2) has a partially significant positive effect on ROA (Y), for LDR risk (X3) does not have a significant negative effect partial to the level of ROA (Y), and for the risk of OEOI (X4) a significant negative effect partially on the level of ROA (Y). It is better if the Regional Development Bank of East Java, must be able to identify the risks that may occur in its business activities. In connection with the results of research where the Bank must minimize NPL, LDR and OEOI ratio because it has a negative effect on ROA. Then maximize NIM because it has a positive effect on ROA.